The Role Of Accounting Information Systems In Improving Management Strategic Decision - Nadya, Wardatun; Muhammad Nawawi; Wahyudi, Tri; Prasadhita, Chandra (Management Science Research Journal, 2024)
This study aims to explain and analyze the role of accounting information systems in improving the quality of management strategic decision-making and analyzing the relationship between the use of accounting information systems and the quality of information and management strategic decision-making. The research method used is descriptive method research. The data source used is secondary data and the data collection method is done through observation, documentation, and literature. The method used in analyzing and processing the collected data is qualitative analysis. Based on the results of the study showed that the accounting information system plays an important role in improving management’s strategic decision-making at PT Krakatau Sarana Properti. The accounting information system provides accurate, timely, and relevant financial and non-financial information so that it can assist management in making strategic decisions to improve company performance. And found several internal and external obstacles: Internal errors such as limited human resource capabilities and skills in using information systems, and external errors such as the security and integrity of financial data that is vulnerable to cyber threats. PT Krakatau Sarana Properti can overcome this well. Keywords: Accounting Information System, Information Quality, Decision-Making, Strategic Management